2013
DOI: 10.19030/jss.v6i1.8244
|View full text |Cite
|
Sign up to set email alerts
|

Impact Of Leadership Styles On Employee Organizational Commitment

Abstract: This research study examines the relationship between transformational, transactional and passive/avoidant leadership styles and three dimensions of organizational commitment – affective, continuance, and normative in two subsidiaries of one multinational organization. The research findings revealed that transformational leadership has the strongest impact on affective commitment, although transactional leadership also affects affective commitment. Transformational leadership also has a significant positive af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 40 publications
1
14
0
2
Order By: Relevance
“…Wiza & Hlanganipai, 2014;Clinebell et al, 2013;Felfe et al, 2010;Castro et al, 2008), which suggest that leadership can foster the development of an emotional attachment to the organization on followers. This attachment can be undertaken conveying a motivational vision, as an expression of an idealized picture based on organizational values and culture (Bass & Avolio, 1993).…”
Section: Enhancing Affective Commitment Through Leadershipmentioning
confidence: 99%
“…Wiza & Hlanganipai, 2014;Clinebell et al, 2013;Felfe et al, 2010;Castro et al, 2008), which suggest that leadership can foster the development of an emotional attachment to the organization on followers. This attachment can be undertaken conveying a motivational vision, as an expression of an idealized picture based on organizational values and culture (Bass & Avolio, 1993).…”
Section: Enhancing Affective Commitment Through Leadershipmentioning
confidence: 99%
“…Many studies have examined the impact of transformational leadership on OC (Avolio et al, 2004; McMurray, Pirola-Merlo, Sarros, & Islam, 2010; Ali, Babar, & Bangash, 2011; Ismail, Mohamed, Sulaiman, Mohamad, & Yusuf, 2011; Riaz et al, 2011; Tuna, Ghazzawi, Tuna, & Çatir, 2011; Atmojo, 2012; Baek-Kyoo, Yoon, & Chang-Wook, 2012; Yeh & Hong, 2012; Clinebell, Skudiene, Trijonyte, & Reardon, 2013; Jackson, Meyer, & Wang, 2013; Bacha, 2014; Yucel, McMillan, & Richard, 2014). A few studies have also shown that other types of leadership lead to OC.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…They focus on the micromanagement of their employees and favour a reward system and passive problem solving methods dealing with employees (Bass, 1990;Bass & Bass, 2008;Tallman, 2012). Programs that help develop transformational leaders versus transactional leaders play a fundamental role in influencing organizational commitment (Bass, 1990;Clinebell et al , 2013). Vries et al, (2009) A continual and consistent program integrated into the employees' work lives is important to retain staff.…”
Section: Leadershipmentioning
confidence: 99%
“…There is a positive correlation between transformational leadership and organizational commitment (Clinebell et al, 2013). Commitment to the organization can be further defmed as an employee's commitment to their co-workers.…”
Section: Commitment To Co-workers and Teamworkmentioning
confidence: 99%
See 1 more Smart Citation